Evaluation of Inhibition Activity of Rosmerinus officinalis plant watery and oily extracts on some pathogenic Microorganisms - Ibrahim, Auroba M.S.; M. Abid , Majeed; Aldean A. alumni, Alla (The Iraqi Journal of Veterinary Medicine, 2009)
This study included evaluation of inhibition activity of watery and oily extracts of Rosmerinusofficinalis plant on some pathogenic microorganisms like Salmonella typhi، Escheichia coli ، Staphylococcusaureus ، Klebsiella pneumoniae، Aeromonas hydrophila ، Candida albicans. The results of oily extract showedmore activity at concentration (40mg/ml) of microorganisms growth inhibition (26, 24,22,18,18)mmrespectively, compared with aqueous extract which recorded (12,12,10,9,8)mm respectively at concentration(200mg/ml). And procedure the qualitative chemical test of some active ingredients in Rosmerinus officinalisplant. The results showed that the plant contan glycosides, alkaloids, flavonoides , phenols, tannins , resins,saponins and comarins